STUDY THE ABILITY STORAGE OF SIX OLIVE FRUIT CULTIVARS GROWN IN ZAKHO REGION - ABDULQADER, SHAYMAA M.; HASAN , NAHLA M. R.; AL-BAMARNY , SARFARAZ F. A. (Journal of Duhok University, 2022)
Green mature olive fruit (Olea europaea L.) of six cvs. (Basheqi, Sorani, Khilkhali, Manzanillo, Chemlali, Frantoio) were harvested from trees grown in Zakho Nursery, Zakho District, Dohuk governorate, Kurdistan region/Iraq. Samples of each cultivar were placed in plastic bags and stored at 6˚C and 85-90%RH for three different periods (2, 3 and 4) months to evaluate their postharvest physiology and quality changes. Estimated were made on parameters such as (weight loss, TSS, total sugar, pulp stone ratio, fruit peel color development, dry weight, fruit decay and oil content). The results showed that Basheqi cv. Superior  other cvs. in weight loss and dry weight, while sorani cv. surpassed significantly in TSS, total sugars. Khilkhali cv. exceeded in pulp stone ratio and fruit peer color development. Chemlali cv. gave the highest value in oil content and fruit decay. After sweetening the fruit, Chemlali and Basheqi cv. recorded significantly maximum value of oil. Prolonged storage period to 3 and 4 months significantly increased weight loss, TSS, total sugar, pulp stone ratio, fruit peer color development, oil content and fruit decay, while decreased dry weight. The maximum dry weight was obtained when fruit stored for 2 months